188 Point-of-care surrogate biomarkers for cervical cancer screening: feasibility of E7 oncoprotein and P16INK4A detection in cervical samples. (18th September 2019) - Leung, SOA; Feldman, S; Elias, K
Abstract : Objectives: As E7 oncoprotein is synthesized in the latter stages of cervical carcinogenesis, it may be a more specific biomarker for dysplasia than Pap and HPV. By sequestering cations, E7 monomers form oligomers detectable by Dynamic Light Scattering (DLS). p16INK4a staining has been used as an adjunct to cytology but not in a point-of-care setting. Our aim is to detect E7 oncoproteins using DLS and p16INK4a using immunodetection in cervical samples. Methods: Protein lysates from HeLa cells, which express E7 and p16INK4a, and third trimester placenta (3TP), which do not express E7 or p16INK4a, were characterized by DLS as well as p16INK4a antibody by Western blot to establish positive and negative reference standards, respectively. Patient samples were profiled by DLS and Western blots and correlated with clinical findings. Results: Addition of 10mM EDTA resulted in a monomorphic peak at ∼75nm in diameter for HeLa that is distinct from 3TP (∼160nm) by DLS, corresponding to a likely E7 oligomer of ∼1100kDa on native Western blot. 60 patient samples have been collected thus far with DLS patterns that roughly correlate to those seen using cell lines. Western blot probed with p16INK4a antibody was positive and negative for patients with dysplasia/cancer and without cervical abnormalities respectively. Conclusions: Preliminary results suggest feasibility of detecting E7 oligomers by DLS and p16INK4a by immunodetection in patient samples and its potential as a point-of-care test. The presence of E7 in patient samples will be confirmed with mass spectrometry and sensitivity and specificity of p16INKa will be determined with additional patient samples.